Interest and prices : (Geldzins und Güterpreise). A study of the causes regulating the value of money - Wicksell, Knut (New York : A. M. Kelley, 1965)
This author explains that the main problem of monetary theory is the rise and fall of prices but the recardian school placed emphasis on the influence of discount policy on the quantity of money.
Bibliographic footnotes.
sju 24/01/2019
Loans
Keywords: Money; Prices; Quantity theory of money; Interest